An FPGA implementation of novel smart antenna algorithm in tracking systems for smart cities. (January 2018) - Thiripurasundari, C.; Sumathy, V.; Thiruvengadam, C.
Highlights: Use mixed-Scaling-Rotation Coordinate Rotation DIgital Computer (MSR-CORDIC) in the beamforming process. Reduce the iteration and computational complexity in calculation using modified CORDIC based on RLS algorithm. MSR CORDIC based RLS algorithm for beamforming can realize based on HDL coding. Abstract: The area of digital signal processing (DSP) faces a great challenge in suppressing the noise and interference in the transmitting signal. A huge number of applications are in need of such control methods for good audio communication, etc., and the most widespread method for achieving this is through COordinate Rotation DIgital Computer (CORDIC) based on QRD-RLS. However, this method requires several iterations for its calculations, and therefore in order to reduce the complexity of the calculations and for faster calculation with a minimum number of iterations, a modified CORDIC based on the QRD-RLS algorithm for the purpose of beamforming is proposed in this paper and named mixed scaling rotation coordinate rotation digital computer (MSR-CORDIC). In this work, beamforming and direction of arrival (DOA) estimation will be achieved using the MSR-CORDIC and MUSIC algorithms respectively. The proposed algorithm is developed using Verilog HDL and implemented using the Xilinx field-programmable gate array (FPGA). In all cases, the proposed algorithm shows remarkable improvement compared with the conventional SCC (space code correlator) beamforming algorithm. Graphical abstract: